LED lighting extends color shelf life for three beef products compared with fluorescent lighting - K.S. Steele; M.J. Weber; Elizabeth A.E. Boyle; A.S. Lobaton-Sulabo; C. Cundith; Y.H. Hiebert; K.A. Abrolat; J.M. Attey; S.D. Clark; D. Johnson (Kansas Agricultural Experiment Station Research Reports, 2012)
Consumers are not able to estimate tenderness, juiciness, or flavor when selecting beef cuts at retail stores. Instead, they rely on color as one of the major criteria to select beef cuts. During refrigerated display, fresh meat color changes and consumers discriminate against discolored meats. Meat items with discoloration must be discounted or discarded, leading to up to 1 billion in revenue loss nationally for the meat industry. Lighting type and intensity have a major impact on the appearance and shelf life of fresh beef in refrigerated retail display. Light emitting diode (LED) lighting offers advantages for display because it is more energy-efficient and generates less heat than fluorescent lights. These advantages may be beneficial for fresh meat color stability. The objective of this study was to determine the effects of LED and fluorescent (FLS) lighting on visual and instrumental meat color and shelf-life properties of three fresh beef products displayed in two retail display cases that were set up to run at similar temperature profiles when case lighting was off prior to the initiation of the study.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; LED light; Shelf life; Fluorescent lighting; Temperature